LARANGAN RIBA DALAM AL-QURAN : ANALISIS SURAH ALI IMRAN AYAT 130 dalam PRAKTIK PINJAMAN ONLINE - Fauzan Ashar Nur Huda; Muhammad Sapil (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2025)
This article aims to examine Surah Ali-Imran verse 130 and its interpretation regarding the prohibition of riba (usury) and its impact, particularly in the context of online lending practices. The study is expected to raise public awareness about the dangers of riba as emphasized in the Qur'an, as well as to help reduce poverty rates and moral degradation caused by it. The broader goal is to promote social harmony, which has often been disrupted due to the prevalence of riba. This study employs a library research method by referring to various relevant literature. The findings reveal three key aspects contained in Surah Ali-Imran verse 130: the urgency of prohibiting riba as reflected in the phrase ad’afan muda’afah, unethical debt collection practices by creditors, and divine consequences for those who persist in or abandon riba. This research reaffirms that riba poses serious social dangers and must be avoided.